Oxi-Inflammatory Stress and Biomolecular Deterioration: A Mysterious Convergence in Post COVID Patients (Journal of Pharmaceutical Negative Results, 2022)
Background: Despite several scientific efforts against COVID 19, conundrum of biomolecular deterioration in Post COVID syndrome patients are still in dark at an unprecedented scale globally and affected the patient’s health multidimensionally. It is conceivable that patients recovered from COVID-19 after second wave are at enhanced risk of secondary complications.Aim: The present study was carried out to estimate the serum vitamin D and total antioxidant activity (TAC) along withmarkers of oxi-inflammatory stress in post COVID patients diagnosed RT-PCR negative after second wave of COVID-19 andto determine their role in predicting secondary complications.Methodology: 50 subjects (30-55 years) of Delhi-NCR region were recruited and categorized into two groups (n=25 in each group; on the basis of their history of COVID infection). By using standard methods, study group parameters were estimated in Post COVID patients and statistically compared it with that of 25 non affected healthy controls by using student’s t-test.Result: Serum CRP, TNF-α, MDA and uric acid levels were significantly high (p<0.05) in Post COVID patients as compared to healthy controls. Conversely, serum vitamin D and TAC levels along with SOD activities were found to be significantly low (P<0.001) in Post COVID patients as compared healthy controls. However, ceruloplasmin level was altered insignificantly (p<0.1) with respect to Group I subjects. Vitamin D levels were positively correlated with TAC and SOD activity (P<0.001) and negatively correlated with MDA, CRP, TNF-α and uric acid levels in post COVID patients.Conclusion: Therefore, the present study emphasizes the dire need of special attention to Post COVID population by providingvitamin D supplementation, antioxidant and mineral rich diet along with adoption of regular aerobic exercise not only to rejuvenate the biomolecular homeostasis but also to reduce oxi-inflammatory stress mediated future complications.